PELATIHAN PENGGUNAAN MICROSOFT EXCEL DI LEMBAGA MA NURUL ISLAM PAKUHAJI TANGERANG BANTEN - Lailatussyarifah; Sitti Ainur Rofiqotul Anisa; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
Microsoft Excel training at MA Nurul Islam Pakuhaji Tangerang Banten was held as an effort to improve the information and communication technology (ICT) competency of students. For this reason, one of the community service groups of Ibrahimy University Situbondo conducted Microsoft Excel training for MA Nurul Islam Pakuhaji students which aimed to improve students' technical skills in using spreadsheet software for data visualization purposes. Microsoft Excel is an application that is widely used, both in educational and professional environments, because it provides various features that support students in processing, analyzing, and presenting data efficiently. This training covers the basics of using Microsoft Excel, such as an introduction to the interface, basic formulas, and data processing with tables. Through this training, students can understand the use of Microsoft Excel regarding data processing and become the first step in equipping students with relevant digital skills in the modern era